(untitled) (KYAMC Journal, 2019)
Background: Chronic kidney disease (CKD) is progressive loss in kidney function over a period of months or years. CKD is an internationally recognized public health problem affecting 5-10% of the world population and day-by-day the number of cases are increasing at an alarming rate. This study was conducted in Khwaja Yunus Ali Medical College Hospital in Enayetpur, Sirajganj. Objectives: To assess serum creatinine, hemoglobin (Hb), urea, red blood cell (RBC), protein creatinine ratio (PCR) and prolactin in CKD patients. Material and Methods: This study included 110 patients, 61 were males and 49 were females and their age range 1 to more than 60 years.The control group also consisted of same number of participants as the patients, who were free from signs and symptoms of kidney disease and prolactin hormone disorders. Results: The study shows that all the biochemical parameters in CKD patients were found to be significantly high compared with control group (P<0.001). Serum prolactin concentrations in CKD patients were also increased significantly compared with control group (P<0.05). It was found that male CKD patients secret more prolactin hormone than male control. Conclusion: Although males are more prone to chronic kidney disease, but the percentage of females is not negligible. All the biochemical parameters and prolactin level changed significantly in the CKD patients. It is interesting that in case of CKD, male’s prolactin secretion becomes higher. KYAMC Journal Vol. 10, No.-2, July 2019, Page 90-94